Emerging Proteins in CRPC: Functional Roles and Clinical Implications - Kong, Piaoping; Zhang, Lingyu; Zhang, Zhengliang; Feng, Kangle; Sang, Yiwen; Duan, Xiuzhi; Liu, Chunhua; Sun, Tao; Tao, Zhihua; Liu, Weiwei (Frontiers in Oncology, 2022)
Prostate cancer (PCa) is the most common cancer in men in the western world, but the lack of specific and sensitive markers often leads to overtreatment of prostate cancer which eventually developed into castration-resistant prostate cancer (CRPC). Novel protein markers for diagnosis and management of CRPC will be promising. In this review, we systematically summarize and discuss the expression pattern of emerging proteins in tissue, cell lines and serum when castration-sensitive prostate cancer (CSPC) progression to CRPC; focus on the proteins involved in CRPC growth, invasion, metastasis, metabolism and immune microenvironment; summarize the current understanding of the regulatory mechanisms of emerging proteins in CSPC progressed to CRPC at the molecular level; and finally summarize the clinical applications of emerging proteins as diagnostic marker, prognostic marker, predictive marker and therapeutic marker.